Probiotics in the prevention of antibiotic-associated diarrhea in the pediatric population - A Systematic Review - Mariana de Sá Osório Dias Maia (2021)
Objectives: The aim of this systematic review is to assess the effectiveness of probiotics in the prevention of AAD in the pediatric population. Methods: A systematic review of randomized controlled trials (RCTs) was conducted for greater level of evidence. Articles were electronically searched in PUBMED, Web of Science, CENTRAL, irrespective of language, publication status, or date of publication. Records were successively selected according to the criteria for eligibility. The quality of each trial was assessed using the Cochrane Risk of Bias Criteria. Results: Five papers were included, between these, three on Lactobacillus rhamnosus GG and two on Lactobacillus reuteri DSM 17938. Results suggest that the concomitant use of Lactobacillus GG was consistently effective in the prevention of AAD, this being statistically significant. Lactobacillus GG reduced the incidence of AAD to one third. RCTs on Lactobacillus reuteri DSM 17938 found no evidence of its prophylactic use for pediatric AAD. However, the authors believe that an extended follow-up would lead to greater conclusions. Conclusions: This systematic review provides evidence to recommend Lactobacillus GG as a preventive measure of AAD in children but Lactobacillus reuteri DSM 17938 was not found to be effective. We encourage further investigation on both probiotics, mainly via randomized controlled trials.